PENGARUH RIWAYAT MEROKOK TERHADAP DERAJAT KEPARAHAN COVID-19: SYSTEMATIC REVIEW DAN META-ANALISIS - Yoga Prasadja,; Mulyanto , Agus; Ichsan , Burhannudin (Jurnal Kesehatan, 2024)
The coronavirus (COVID-19) pandemic has presented a significant public health threat, posing an immediate risk to the health of the global population and creating far-reaching long-term consequences. The main disorder that is often caused by COVID-19 is the respiratory system, so smoking and cigarette use can be categorized as people who have a high risk of developing severe lung infections. Smoking is associated with a higher chance of developing a critical illness and a higher chance of dying from the COVID-19 disease. This study aims to analyze the effect of smoking history on the severity of COVID-19. This study uses a systematic review and meta-analysis design. Screening articles using the PRISMA method, from 2,014 articles, 9 articles were obtained that met the restriction criteria. Based on the results of a systematic review that has been carried out on the influence of a history of smoking on the severity of COVID-19, it shows that a history of smoking can develop a critical illness that requires mechanical ventilation, developing the classic triad of symptoms that indicate a diagnosis of COVID-19 (fever, persistent cough and shortness of breath). , increased burden of COVID-19 symptoms, ICU admission, need for intubation, increased frequency of ACE2 genotype and had a higher risk of death. Active smoking and smoking history significantly increased the severity and mortality of COVID-19 (OR= 2.59; p= 0.006).